2014
DOI: 10.1186/s12913-014-0560-y
|View full text |Cite
|
Sign up to set email alerts
|

Poverty and health care demand in Kenya

Abstract: BackgroundThere is a wide range of actions an individual could take when sick or injured such as self–care, consulting a traditional healer, or seeking treatment from a private or public health care facility. The specific action taken is influenced by individual characteristics, provider characteristics, societal factors, and geographical factors. A key individual characteristic is the ability to afford the required health care. The study examines the effect of poverty on an individual’s choice of a health car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
44
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 52 publications
5
44
0
1
Order By: Relevance
“…Households with an educated head were less likely to forgo care due to cost. Furthermore, lack of formal education is seen as a predictor of poverty given education opens up a range of income-generating opportunities [60]. Other studies have also reported lower levels of education increases the odds of having unmet need [61].…”
Section: Discussionmentioning
confidence: 99%
“…Households with an educated head were less likely to forgo care due to cost. Furthermore, lack of formal education is seen as a predictor of poverty given education opens up a range of income-generating opportunities [60]. Other studies have also reported lower levels of education increases the odds of having unmet need [61].…”
Section: Discussionmentioning
confidence: 99%
“…Introduction Achieving the best health status possible is one of the most important social goals world-wide. This is because health is a human right as well as a valued asset necessary for improved productivity (Awiti, 2014). In case of poor health, an individual is faced with a wide variety of actions that he/she can undertake to improve health.…”
mentioning
confidence: 99%
“…For instance, in Kenya, poverty reduced the probability of infants and children aged 1-14 from visiting modern healthcare facilities. [19] Poverty is a barrier to the poor in accessing healthcare services in developing countries. [20] Where there are no social health insurance schemes for low-income earners, remittances serve as a substitute for those that have international migrants that are sending money to them.…”
Section: Discussionmentioning
confidence: 99%